Occurrence and Distribution of Microplastics in Sediments of the Miri Coastal Environment, Northwest Borneo - Mishra, Anshuman (Curtin University, 2024)
This study investigates the microplastics (MPs) in the sediments of Miri coastal environment. This research unveils the spatial and temporal variations of MPs based on physical and chemical characteristics to determine the potential source materials of MPs. This study also reveals the bioaccumulation of MPs in a few marine organisms of this region. The outcome of this study establishes a link with the UN Sustainable Development Goals, which emphasizes the significance of the study.